1978
DOI: 10.1084/jem.148.5.1161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of clonal abortion tolerogenesis. I. Response of immature hapten- specific B lymphocytes

Abstract: B lymphocytes with receptors specific for the hapten fluorescein (FLU) were prepared from the spleens of mice of various ages. For most experiments, a one-step fractionation procedure based on the adherence of FLU-specific cells to FLU-gelatin was used. For some experiments, a subset of higher FLU-binding capacity was prepared from the FLU-gelatin binding population through the use of the fluorescence-activated cell sorter (FACS). FLU-specific B cells were placed into microculture with either FLU(3.6)-human ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…Results from several early experiments have shown that immature B cells that are isolated from neonates or adult spleens or grown in BM cultures, respond to stimulation with LPS by proliferation and antibody production [22][23][24][25][26]. These findings suggest that immature B cells are responsive to mitogenic stimuli.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Results from several early experiments have shown that immature B cells that are isolated from neonates or adult spleens or grown in BM cultures, respond to stimulation with LPS by proliferation and antibody production [22][23][24][25][26]. These findings suggest that immature B cells are responsive to mitogenic stimuli.…”
Section: Introductionmentioning
confidence: 65%
“…The in vitro and the ex vivo data obtained from our experiments suggest that these nontolerant immature B cells can be driven to secrete autoantibodies in response to stimulation with CpG DNA and with LPS (data not shown). Although LPS has been shown to activate immature B cells to secrete IgM antibodies [22][23][24][25][26], it is now clear that a significant proportion of these cells are autoreactive. Our results, therefore, suggest that developing B cells in the BM are responsive to TLR stimuli and that such activation is physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Since LPS has been shown to interfere with B-cell tolerance induction, [11][12][13] we examined its ability to overcome the unresponsiveness of immature B cells to BCR cross-linking in vitro. Immature B cells (purified from the spleens of 2-3-dayold mice) and mature B cells (from 8-10-week-old mice) were cultured for 48 hr with no stimulus, 50 m g/ml of goat anti-m F(ab') 2 fragments, 50 m g/ml of LPS, or anti-m plus LPS.…”
Section: Lps Allows Immature B Cells To Proliferate In Response To Bcmentioning
confidence: 99%
“…For example, unresponsiveness induced in adult animals by polysaccharides or deaggregated proteins can be overcome by administration of LPS within several days of exposure to the tolerogen. 11,12 In addition, LPS can prevent clonal deletion of immature B cells in response to antigen 13 and growth inhibition of immature B-cell lines in response to antiimmunoglobulin stimulation. 14 Finally, in transgenic models of Bcell clonal anergy, LPS stimulation has been shown to partially overcome the anergic state.…”
mentioning
confidence: 99%
“…Processes that occur during B cell development shape that balance and give rise to a very nonrandom repertoire of new B cells even before exposure to foreign Ag. The best defined of the early processes are those that test for effective association of a -chain with pseudo L chain (1,2) and those that abrogate potentially damaging autoreactivity by cell deletion, anergy, or receptor editing (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%